Tests of Language Proficiency: Kannada - (:unkn) unknown (My University, 2003)
The present volume is one of the constituents of the proficiency test series in the Kannada Language. The concept of proficiency is also differentiated from other related concepts such as achievement, aptitude, etc.
Keywords: Kannada; English